Production of Single-Cell Oil from a Local Isolate Bacillus subtilis Using Palm Fronds - Wassan Dawood Musa Al-Obeidi; Dhafer F. Al-Rawi; Loay H. Ali (International Journal of Biomaterials)
This study, conducted at the Department of Biology, University of Anbar, Iraq, focuses on addressing the escalating issue of contamination and aims to acquire microbial oils to alleviate the global shortage in plant and animal oil production, utilizing environmental waste as a carbon source to reduce global pollution and select efficient local bacterial isolates of Bacillus subtilis for the production of single-cell oil (SCO) using local soil and environmental waste as a carbon source. Four isolates were selected as the best in producing single-cell oil, with the isolate with code C4 standing out as it recorded the highest production. It is worth noting that all these isolates belong to the bacteria type Bacillus subtilis. Palm fronds were found to be the most suitable environmental residue for SCO production compared to other waste materials (wheat straw and wheat bran). Submerged cultures were used to improve SCO production, with optimal conditions determined as pH 7, a temperature of 30°C, carbon source concentration of 3 g/100 ml, inoculum volume of 3 ml/100 ml, inoculum density of 20 × 107 cells, and an incubation period of 72 hours. The Soxhlet extraction method was used to obtain the oil, which was found to contain high percentages of unsaturated fatty acids, particularly linoleic acid (46.030%) and palmitoleic acid (16.579%). The oil was highly soluble in chloroform and ethanol but insoluble in water. The saponification test indicated the potential for soap production from the oil. This comprehensive research addresses the need for locally sourced and sustainable SCO production, offering insights into the selection of efficient bacterial isolates, the optimization of cultivation conditions, and the valuable properties of the resulting SCO. The significance of this study lies in the production of single-cell oil from soil-isolated Bacillus subtilis bacteria for use in food applications.